Development of non-invasive ventilation treatment practice for patients with chronic obstructive pulmonary disease:Results from a participatory research project. (8th November 2017) - Christensen, Helle M; Titlestad, Ingrid L; Huniche, Lotte
Objectives: Non-invasive ventilation treatment for patients with acute exacerbation of chronic obstructive pulmonary disease is well documented. Communication with patients during treatment is inhibited because of the mask, the noise from the machine and patient distress. Assessing life expectancy and identifying end-stage chronic obstructive pulmonary disease posed difficulties and caused doubts concerning initiation and continuation of non-invasive ventilation as life-sustaining treatment. Health professionals expressed a need for knowledge of patients' perspectives and attitude towards non-invasive ventilation. Methods: The study adheres to principles of Critical psychological practice research. Data on patients' and health professionals' perspectives were obtained from observations from the ward and semi-structured interviews with 16 patients. A group of health professionals was set up to form a co-researcher group. The co-researcher group described and analysed treatment practice at the department, drawing on research literature, results from observations and patients' interviews. Results: Interviews revealed that 15 patients evaluated treatment with non-invasive ventilation positively, although 13 had experienced fear and 14 discomfort during treatment. The co-researcher group described health professionals' perspectives and analysed treatment practice based on data from patients' perspectives developing new management strategies in clinical practice with non-invasive ventilation. Conclusion: The participatory approach enabled continuous and complementary development of knowledge and treatment practice. The investigation of patient perspectives was particularly productive in qualifying cooperation among health professionals. The study resulted in preparing, and implementing, new clinical strategies.